Zapisz w jak najprostszej postaci
a) (a+b)-(2a-b)-(a-2b)
b) (3x-y+1)-(x+y)+(y-x)
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)
d) (2ab+a+3)-(3ab-a+3)
e) (4x do kwadratu-3x)-(x+0,1x do kwadratu)-(x do kwadratu-0,1x)

a) 4x-(x+6)+4 dla x=1/3
b) (x do kwadratu+1)-(x do kwadratu-2)+10 dla x= 2,2
c) (a+4b)-(5+2a)-(3b-5) dla a= 0,1 i b=0,2

3

Odpowiedzi

2010-02-07T17:38:04+01:00

Zapisz w jak najprostszej postaci
a) (a+b)-(2a-b)-(a-2b)=a+b-2a+b-a+2b=4a+4b
b) (3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x-y+1
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)=-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
d) (2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab+a-3=-ab+2a
e) (4x do kwadratu-3x)-(x+0,1x do kwadratu)-(x do kwadratu-0,1x)=16x²-3x-x-0,1²-x²-0,1x=15x²-4,1x-0,01

a) 4x-(x+6)+4 dla x=1/3 = 4*⅓-(⅓+6)+4=⁴/³-6⅓+4=-4
b) (x do kwadratu+1)-(x do kwadratu-2)+10 dla x= 2,2
c) (a+4b)-(5+2a)-(3b-5) dla a= 0,1 i b=0,2
2 4 2
2010-02-07T17:40:36+01:00
A) (a+b)-(2a-b)-(a-2b)=a+b-2a+b-a+2b=-2a+4b
b) (3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x-y+1
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny)=-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
d) (2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab+a-3=-ab+2a
e) (4x do kwadratu-3x)-(x+0,1x do kwadratu)-(x do kwadratu-0,1x) =4x⁴-3x-x-(0,1x)²-x²+0,1x=4x⁴-x²-4x-(0,1x)²+0,1x=0,1x(1-x)+4x(x³-x-1)

a) 4x-(x+6)+4 dla x=1/3 = 4x-x-6+4=3x-2=3(1/3)-2=-1
b) (x do kwadratu+1)-(x do kwadratu-2)+10 dla x= 2,2=(2,2)²+1-(2,2)²+2=3
c) (a+4b)-(5+2a)-(3b-5) dla a= 0,1 i b=0,2 =a+4b-5-2a-3b+5=-a+b=-0,1+0,2=0,1
2 4 2
2010-02-07T23:26:19+01:00
A) (a+b)-(2a-b)-(a-2b) = a+b-2a+b-a+2b = -2a+4b
b) (3x-y+1)-(x+y)+(y-x) = 3x-y+1-x-y+y-x = x-y+1
c) -(kx+ny)-(3kx+2ny)+(5kx-3ny) = -kx-ny-3kx-2ny+5kx-3ny = kx-6ny
d) (2ab+a+3)-(3ab-a+3) = 2ab+a+3-3ab+a-3 = -ab+2a
e) (4x do kwadratu-3x)-(x+0,1x do kwadratu)-(x do kwadratu-0,1x) = 4x²-3x-x-0,1x²-x²+0,1x = 2,9x²-3,9x

a)
4x-(x+6)+4 =
4*1/3-1/3-6+4 =
4/3-1/3-6+4 =
1-6+4 = -1
b)
(x do kwadratu+1)-(x do kwadratu-2)+10 =
2,2²+1-2,2²+2+10 =
4,84+1-4,84+2+10 = 13
c)
(a+4b)-(5+2a)-(3b-5) =
0,1+4*0,2-5-2*0,1-3*0,2+5 =
0,1+0,8-5-0,2-0,6+5 = 0,1




3 5 3